Analisis Hukum Pencatatan Perkawinan Kewarganegaraan Yang Berbeda (Studi Kasus Kua Tanjung Pura) - Era Fazira; Alang Sidek (Peduli Riset dan Pengabdian Masyarakat, 2025)
This study aims to analyze the legal regulations and implementation of marriage registration between citizens of different nationalities, as well as the obstacles encountered in practice, in order to provide legal certainty for the parties involved, particularly at the Religious Affairs Office (KUA) of Tanjung Pura District. Marriages between citizens of different nationalities are a consequence of increased population mobility and cross-border interactions in the era of globalization, which raise legal issues related to the validity of marriage, administrative order, citizenship status, and the protection of the rights of husbands, wives, and children. This study uses a normative-empirical legal research type with a descriptive-analytical method. The approaches used include legislative, conceptual, and sociological approaches. Data was obtained through a literature study of laws and regulations governing marriage, citizenship, and population administration, as well as empirical data through interviews with the Head of the KUA, Marriage Registrar, spouses of different nationalities, and community leaders, as well as documentation related to marriage registration. The results of the study show that the registration of marriages between citizens of different nationalities requires more detailed special administrative requirements, especially regarding citizenship documents and letters of no impediment to marriage from the foreign national's country of origin. Legal regulations in Indonesia have basically provided a clear legal basis and protection for the parties. The implementation of marriage registration between citizens of different nationalities at the Tanjung Pura KUA is generally in accordance with applicable regulations, but there are still administrative obstacles and limitations in public understanding, so that efforts are needed to raise awareness and improve services in order to achieve optimal legal certainty.